Complete mitochondrial genome of Pseudocrangonyx joolaei (Crustacea: Amphipoda: Pseudocrangonyctidae) - Chi-Woo Lee; Takafumi Nakano; Ko Tomikawa; Gi-Sik Min (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitochondrial genome of a subterranean pseudocrangonyctid amphipod, Pseudocrangonyx joolaei, was determined in this paper. The complete mitogenome of P. joolaei was 14,814 bp in length with the typical 13 protein-coding genes, 22 transfer RNAs, two ribosomal RNAs, and a control region (CR). The gene order of P. joolaei was unique in that the CR was an inversion, and the gene order of Pseudocrangonyx was not concordant when compared to that of P. daejeonensis, a subterranean amphipod found in Korea. A maximum-likelihood tree, constructed based on 26 eumalacostracan mitogenomes, confirmed that P. joolaei supported monophyly in the family Pseudocrangonyctidae and is most closely related to the superfamily Crangonyctoidea.